Cambrian–Silurian sediments in the southeastern Qilian Orogen, NE Tibetan Plateau: Constraints on crustal and tectonic evolution of microcontinents in the northern Proto-Tethys Ocean. (1st July 2022) - Li, Xi-Yao; Li, Sanzhong; Yu, Shengyao; Liu, Yongjiang; Guo, Xiao-Yu; Huang, Zeng-Bao; Zhao, Shujuan; Cao, Huahua
Graphical abstract: Highlights: Early Paleozoic crustal growth in the Qilian Orogen was linked to subduction surrounding microcontinent in the northern Proto-Tethys Ocean. A close affinity between the Qilian, North Qinling, Indochina, and South China blocks along the northern margin of Gondwana during the Early Paleozoic. Between the Ordovician and Silurian, sedimentary basins evolved from inter- and back-arc basins to retro -arc foreland basins, and finally to foreland basins. Abstract: The Qilian Orogen preserves abundant Early Paleozoic records, revealing the tectonic evolution of the northern Proto-Tethys Ocean on the periphery of the northern margin of eastern Gondwana. We present detrital zircon U–Pb and Hf isotopes, and whole-rock element and Nd isotopic geochemical data on the Early Paleozoic sedimentary rocks in the southeastern Qilian Orogen. Detrital zircon grains from these rocks are clustered into seven distinct age groups: 495–426 Ma, 710–501 Ma, 1043–726 Ma, 1347–1054 Ma, 2009–1609 Ma, 2874–2274 Ma, and >3100 Ma. Detrital zircon and geochemical results suggest that their provenances are Early Paleozoic subduction–accretion related rocks, Neoproterozoic basements of the Qilian Block, and recycled sediments from Precambrian units. The whole-rock εNd (t) values of the sedimentary samples range from –13.0 to 2.5, and the εHf (t) values of Neoproterozoic–Early Paleozoic detrital zircon grains range from –28.6 to 15. Hf and Nd isotopes indicate marked growth and reworking of the continental crust in the early Neoproterozoic and Ordovician–Early Silurian. As revealed by age spectra of detrital zircon, we infer that the Qilian Block was tectonically related to blocks on the northern margin of eastern Gondwana during the Early Paleozoic, such as the North Qinling, Indochina and South China blocks. We also suggested that the Qilian Block experienced double-sided subduction of the North and South Qilian oceans, and developed sedimentation in the inter-arc and back-arc basins during the Ordovician to earliest Silurian. Finally, sedimentation occurred in an Early Silurian retro -arc foreland basin and Middle Silurian foreland basin during the syn -collisional stage.